PENGARUH IKLIM KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) CABANG SEMARANG SELATAN - Nikolas Prima Ginting; Turnomo Rahardjo; Tandiyo Pradekso; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2015)
Communication climate in organization taking objective in the internal environment of an organization that includes members of the organization's perception based on the events that occur within the organization. conducive and democratic communication atmosphere in an organization made employee satisfactied of their works, made a positive performance and then produce willingness to seek a high level of performance, and facilitate the achievement of corporate goals.The goal of this research is to explain the influence of communication climate on employee performance in Regional Water Company (Perusahaan Daerah Air Minum - PDAM) South Semarang branch. Using a quantitative approach based questionnaire, based on five critical dimensions of communication climate that will be analyzed by the method / theory of science communication climate inventory developed by Peterson and pace (1976)Based on the analysis of data using Kendall tau correlation and the overall results of research, this study produce the conclusion that there is a relationship or correlation between organizational communication climate with PDAM employee performance semarang southern branch. The hypothesis stated that there is a significant relationship between organizational communication climate influence on employee performance. Employees found that organizational communication climate in the company is well run and effectiveAdvice can be given by researchers that the company should pay more attention to supporting factors to improve communication climate in the office, such as supportivenes behavior that used to observe that their communication with the boss to help them build and maintain confidence, can participate, transparency, trustworthy. Employees should be able to create a good atmosphere of the communication quality, both among fellow employees and the office leader to make each individual within the company to trust each other, motivate each other, and cooperate in running the tasks and responsibilities of the job. Employees should be more focused and strive to create harmony in the work, for example by building solid teamwork and also can cooperate with each other to settle the improvement to employee’s job satisfaction